Arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel and preparation method and application thereof

CN117700911BActive Publication Date: 2026-10-27SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311775649.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2026-10-27
Estimated Expiration
2043-12-21

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种精氨酸改性淀粉/聚丙烯酸/碳纳米管/银纳米线水凝胶及其制备方法和应用,以解决淀粉基水凝胶机械强度差、体积稳定性差、凝胶网络中分子链相互作用弱、导电性差、传感灵敏度弱的技术问题

Benefits of technology

[0023]本发明公开了一种精氨酸改性淀粉/聚丙烯酸/碳纳米管/银纳米线水凝胶,该精氨酸改性淀粉/聚丙烯酸/碳纳米管/银纳米线水凝胶的应变灵敏度为2~4.5,水凝胶中存在着丙烯酸与N,N-亚甲基双丙烯酰胺聚合后形成的共价交联结构,存在着精氨酸改性玉米淀粉中的羧基与玉米淀粉结构单元羟基之间形成的离子键交联结构,存在着淀粉中羟基与聚羧酸分子链中羧基及精氨酸结构中氨基之间离子键形成的交联结构,同时这些多个极性基团之间也存在着分子间作用力形成的交联结构。因此本发明制备的淀粉基水凝胶中存在着多个交联网状结构相互穿插相互交织的网状结构,所制备的淀粉基水凝胶具有体积稳定性好、机械强度较大及自修复等特点。同时在淀粉水凝胶中穿插嵌入有碳纳米管及银纳米线形成的复合导电传感体系,使得碳纳米管/银纳米线复合物嵌入在淀粉水凝胶中不易移动,具有对于环境的刺激响应性好、传感的灵敏度高的性能特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117700911B_ABST
    Figure CN117700911B_ABST
Patent Text Reader

Abstract

The application discloses arginine modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel and a preparation method and application thereof. The method is that, in an arginine modified corn starch solution, a free radical polymerization reaction is carried out with acrylic acid as a polymer monomer, N,N-methylene bisacrylamide as a crosslinking agent and ammonium persulfate as an initiator; carbon nanotube / silver nanowire compounds are added in the reaction process; and finally, the arginine modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel is obtained. In the prepared hydrogel, various network structures of mutual penetration and interweaving exist between polyacrylic acid and modified starch, so that the prepared hydrogel has good mechanical strength and volume stability. The double-conductive network formed by the carbon nanotube and the silver nanowire has stable and sensitive electric signal sensing performance. The raw materials are easy to obtain, the cost is relatively low, and the preparation process is unique and simple, so that the hydrogel has wide application in flexible wearable electronic devices and flexible electronic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of starch-based smart hydrogel functional polymer material preparation technology, specifically relating to an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, its preparation method, and its application. Background Technology

[0002] Smart materials are novel functional materials capable of sensing external stimuli (such as pH, temperature, light, humidity, electricity, magnetic fields, force, or biological stimuli), judging and appropriately processing them, and performing their own actions. Artificial intelligence is a crucial direction for current and future development, and smart materials are a vital material foundation supporting AI. Various smart sensors, electronic skin, artificial muscles, and smart drug carriers all rely on corresponding smart materials to function. Traditional smart materials are mainly metal alloys, inorganic compounds, and polymers. These materials have various drawbacks when used to prepare wearable smart materials. For example, metallic smart materials have poor wearing comfort, inorganic compounds have poor environmental adaptability and biocompatibility, and synthetic polymers suffer from degradation, slow response speed, and poor biological performance. In contrast, biomaterials with sensitive responses to environmental stimuli have attracted great interest from researchers. Biomass materials, with their biodegradability and environmental stimulus responsiveness, have become ideal candidates for constructing novel smart materials and a structural guide for their development.

[0003] With the rapid development and application of intelligent wearable sensors, the demand for flexible electrolytes with ion transport capabilities, characterized by high tensile strength, high compressibility, and high sensitivity, is constantly increasing. Compared to metals and inorganic and synthetic polymer conductive materials, conductive hydrogels possess high tensile strength, high flexibility, and better environmental adaptability, making them more suitable for the fabrication of flexible electronic devices. Hydrogels based on natural polymers, in addition to their safety, biocompatibility, and sustainability, can easily achieve conductivity by adding electrolytes, attracting increasing interest from researchers. However, pure natural polymer-based hydrogels typically exhibit low tensile strength (<100%) and compressibility (<75%), significantly limiting practical applications. Starch is the most abundant and widely used natural polymer material, and intelligent hydrogels based on natural starch have attracted considerable attention.

[0004] To address the technical problems of starch-based conductive hydrogels, such as poor mechanical strength, weak molecular chain interactions in the gel network leading to poor volume stability, poor conductivity and sensitivity, and poor sensing performance, there is an urgent need to develop starch-based smart hydrogel materials with good mechanical properties, volume stability, conductivity and sensitivity, and environmental responsiveness. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, its preparation method and application, so as to solve the technical problems of poor mechanical strength, poor volume stability, weak molecular chain interaction in the gel network, poor conductivity and weak sensing sensitivity of starch-based hydrogels.

[0006] To achieve the above objectives, the present invention employs the following technical solution:

[0007] This invention discloses an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, the structural formula of which is as follows:

[0008]

[0009] This invention also discloses a method for preparing the above-mentioned arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, comprising the following steps:

[0010] 1) Dissolve corn starch in water, add sodium periodate, adjust the pH to 3-5, react in the dark, filter, wash and dry to obtain dialdehyde corn starch.

[0011] 2) Add the dialdehyde corn starch obtained in step 1) to a mixture of ethanol and water, then add arginine, stir and react, add ethanol, and then evaporate by rotary evaporation to obtain arginine-modified starch.

[0012] 3) Add polyvinylpyrrolidone and carbon nanotubes to heated ethylene glycol, stir evenly, add a mixed solution of ethylene glycol and FeCl3 and a mixed solution of ethylene glycol and AgNO3, keep the reaction at the temperature, add acetone solution, let stand to remove the supernatant, wash by centrifugation, and dry under vacuum to obtain carbon nanotube / silver nanowire composite.

[0013] 4) Dissolve the arginine-modified starch obtained in step 2) in water by stirring, add N,N-methylenebisacrylamide and ammonium persulfate, stir evenly, start adding acrylic acid dropwise, then add the carbon nanotube / silver nanowire composite obtained in step 3), stir and react, purge under nitrogen, and after ultraviolet irradiation, obtain arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel.

[0014] Preferably, in step 1), the mass ratio of corn starch:water:sodium periodate is (5-15):(150-200):(2-4); the reaction temperature is 25-30°C and the reaction time is 4-6 hours; the drying conditions are vacuum drying at 45-50°C for 3-8 hours; and the molecular weight of corn starch is 16,000-500,000.

[0015] Preferably, in step 1), the pH value is adjusted using a dilute hydrochloric acid solution with a mass fraction of 16% to 20%; the washing conditions are: washing three times with water and acetone in sequence, with the mass ratio of water to acetone being (20 to 30): (30 to 40).

[0016] Preferably, in step 2), the mass ratio of dialdehyde corn starch to arginine is (1-2):(0.03-0.2); in the mixture of ethanol and water, the mass ratio of ethanol to water is (10-20):(20-30), and the purity of ethanol is 95%; the stirring reaction temperature is 25-30°C, the stirring reaction time is 2-4 hours, and the rotary evaporation temperature is 60-70°C.

[0017] Preferably, in step 3), the mass ratio of polyvinylpyrrolidone: carbon nanotubes: FeCl3: AgNO3 is (1-2):(0.1-0.2):(0.1-0.3):(0.3-0.5); 100-200 parts by mass of ethylene glycol and 100-150 ml of acetone are added to every 0.1-0.2 parts by mass of carbon nanotubes; every 0.1-0.3 parts by mass of FeCl3 is mixed with 10-20 parts by mass of ethylene glycol; every 1.2-2 parts by mass of AgNO3 is mixed with 10-30 parts by mass of ethylene glycol; the mixture is allowed to stand for 20-24 hours to remove the supernatant, centrifuged and washed, then washed with anhydrous ethanol, and after washing three times, it is dried under vacuum at 60-70°C.

[0018] Preferably, in step 3), the carbon nanotubes comprise 95% by mass, are single-arm carbon nanotubes, have a conductivity greater than 2000 S / cm, and a specific surface area greater than 980 m². 2 / g; the mass percentage of silver nanowires is 95%, the diameter of the silver nanowires is 90nm, and the length of the silver nanowires is 50um; the heating temperature is 150~170℃; the stirring conditions are stirring at 150~170℃ for 1~1.5 hours; the heat preservation reaction conditions are reacting at 150~170℃ for 2~2.5 hours; the standing time is 20~24 hours; the number of washing times is 3~5 times.

[0019] Preferably, in step 4), the mass ratio of arginine-modified starch: N,N-methylenebisacrylamide: ammonium persulfate: acrylic acid: carbon nanotube / silver nanowire composite is (0.2-1.0): (0.01-0.04): (0.02-0.08): (2-5): (0.004-0.008). During preparation, 0.2-1.0 parts by mass of arginine-modified starch are first dissolved in 50-70 parts by mass of water.

[0020] Preferably, in step 4), the stirring reaction time is 30-40 minutes; the nitrogen purging time is 10-15 minutes; and the ultraviolet irradiation time is 60-120 minutes.

[0021] This invention also discloses the application of the above-mentioned arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel in conductive sensing.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] This invention discloses an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel. The strain sensitivity of this arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel is 2–4.5. The hydrogel contains covalently cross-linked structures formed by the polymerization of acrylic acid and N,N-methylenebisacrylamide, ionic cross-linked structures formed between the carboxyl groups in the arginine-modified corn starch and the hydroxyl groups of the corn starch structural units, and ionic cross-linked structures formed between the hydroxyl groups in the starch, the carboxyl groups in the polycarboxylic acid molecular chain, and the amino groups in the arginine structure. Simultaneously, intermolecular forces also exist between these multiple polar groups to form cross-linked structures. Therefore, the starch-based hydrogel prepared by this invention contains multiple interwoven cross-linked network structures, exhibiting good volume stability, high mechanical strength, and self-healing properties. Furthermore, the composite conductive sensing system formed by carbon nanotubes and silver nanowires embedded within the starch hydrogel makes the carbon nanotube / silver nanowire composite embedded in the starch hydrogel less prone to movement, resulting in good responsiveness to environmental stimuli and high sensing sensitivity.

[0024] This invention also discloses a method for preparing the aforementioned arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel. The method first uses sodium periodate to oxidize corn starch to prepare dialdehyde corn starch. Then, the amino group of arginine undergoes an aldehyde-amine condensation reaction with the aldehyde group in the dialdehyde corn starch to form arginine-grafted modified starch. This starch is then placed in a polymerization reaction consisting of acrylic acid, N,N-methylenebisacrylamide, and ammonium persulfate. A carbon nanotube / silver nanowire composite is added during the polymerization reaction to prepare the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire composite hydrogel. The prepared hydrogel contains a cross-linking system formed by covalent bonds, a cross-linking system formed by ionic bonds, a cross-linking system formed by hydrogen bonds, and a network system formed by intermolecular forces. These network systems interweave and intertwine with each other, thus exhibiting good mechanical strength and volume stability, and stable and sensitive electrical signal sensing performance. This effectively improves the shortcomings of existing starch-based hydrogels, such as poor mechanical strength, weak molecular chain interactions in the gel network, and poor sensing performance. The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel of this invention exhibits good electrical conductivity and sensing properties, with an optimal GF of 4.5. The corn starch used in this invention is a natural biomass with a market price of 8.4 yuan / kg and acrylic acid is 13 yuan / kg, making it inexpensive and readily available. It can replace expensive medical sensors costing hundreds of thousands of yuan in everyday life, with a total cost of only 2 yuan per test. Therefore, it features readily available raw materials, low cost, and a unique and simple preparation process. The prepared hydrogel has wide applications in flexible wearable electronic devices and flexible electronic materials.

[0025] The present invention also discloses the application of the above-mentioned arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel in conductive sensing. The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel is used in an electrochemical workstation and has the characteristics of high strength, good volume stability and high strain sensitivity (GF = 2 to 4.5). Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the reaction of the dialdehyde corn starch disclosed in this invention;

[0027] Figure 2 This is a schematic diagram of the reaction of arginine-modified starch disclosed in this invention;

[0028] Figure 3 This is a schematic diagram illustrating the synthesis of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel disclosed in this invention.

[0029] Figure 4 The infrared spectra of corn starch, dialdehyde corn starch and arginine-modified starch, the raw materials disclosed in this invention;

[0030] Figure 5Infrared spectra of the corn starch hydrogel, arginine-modified starch hydrogel, and arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel disclosed in this invention. Detailed Implementation

[0031] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0032] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0033] The present invention will now be described in further detail with reference to the accompanying drawings:

[0034] This invention discloses an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel and its preparation method. The method involves sequentially modifying corn starch with sodium periodate and arginine, followed by free radical polymerization of acrylic acid, N,N-methylenebisacrylamide, and ammonium persulfate in the presence of the modified corn starch. Simultaneously, a carbon nanotube / silver nanowire composite is introduced, and various cross-linked networks are formed through covalent cross-linking, ionic cross-linking, hydrogen cross-linking, and intermolecular forces. The prepared arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel exhibits high strength, good volume stability, high conductivity, and high sensing sensitivity.

[0035] This invention discloses a method for preparing arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, which specifically includes the following steps:

[0036] Step 1: Take 5-15 parts by weight of corn starch with a molecular weight of 16,000-500,000, add 150-200 parts of water and stir, then add 2-4 parts of sodium periodate powder, adjust the pH value to 3-5 with 16%-20% hydrochloric acid solution, react at 25-30°C in the dark for 4-6 hours, wash and filter with 20-30 parts of water and 30-40 parts of acetone, and vacuum dry at 45-50°C for 3-8 hours to obtain dialdehyde corn starch;

[0037] Step 2: By mass, add 1-2 parts of the dialdehyde corn starch obtained in Step 1 to 20-30 parts of water and 10-20 parts of ethanol, stir at 25-30°C, add 0.03-0.2 parts of arginine, and continue the reaction for 2-4 hours; add 40-60 ml of ethanol, and use a rotary evaporator to evaporate the water at 60-70°C. Add 100-200 ml of ethanol to the evaporated liquid until a milky white solid precipitates, and filter to obtain arginine-modified starch;

[0038] Step 3: By mass, heat 100–200 parts of ethylene glycol at 150–170°C for 1–1.5 hours, then simultaneously add 1–2 parts of polyvinylpyrrolidone and 0.1–0.2 parts of carbon nanotubes. Stir rapidly at 150–170°C for 1–1.5 hours, then add 10–20 parts of a mixture of 600 mol / L ethylene glycol and 0.1–0.3 parts of FeCl3, and 10–30 parts of a mixed solution of ethylene glycol and 1.2–2 parts of AgNO3. Heat at 150–170°C... The reaction was continued at 170℃ for 2–2.5 hours. After the solution cooled to room temperature, 100–150 mL of acetone solution was added, and the mixture was allowed to stand for 20–24 hours. The supernatant was then removed, and the mixture was washed 3–5 times by centrifugation with 40–50 parts of ethanol. The final product was obtained by vacuum drying at 60–70℃ to obtain a carbon nanotube / silver nanowire composite. The composite contained 95% carbon nanotubes by mass, all of which were single-arm carbon nanotubes. The conductivity of the carbon nanotubes was greater than 2000 S / cm, and the specific surface area was greater than 980 m². 2 / g; The mass percentage of silver nanowires is 95%, the diameter of silver nanowires is 90nm, and the length of silver nanowires is 50um;

[0039] Step four: By mass, add 0.2–1.0 parts of the arginine-modified starch obtained in Step two to 50–70 parts of water and stir to dissolve. Add 0.01–0.04 parts of N,N-methylenebisacrylamide and 0.02–0.08 parts of ammonium persulfate, and then slowly add 2–5 parts of acrylic acid. 20–30 minutes after the addition of acrylic acid begins, add 0.004–0.008 parts of carbon nanotube / silver nanowire composite. The acrylic acid is added over a period of 40–60 minutes. After all the acrylic acid has been added, continue the reaction for 30–40 minutes. Treat the solution with nitrogen for 10–15 minutes and irradiate it under ultraviolet light for 60–120 minutes to obtain an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel.

[0040] Example 1

[0041] A method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, specifically including the following steps:

[0042] Step 1: Take 5 parts by mass of corn starch with a molecular weight of 16,000, add 150 parts of water and stir, add 2 parts of sodium periodate powder, adjust the pH value to 3 with 16% hydrochloric acid solution, react at 25°C in the dark for 4 hours, filter with 20 parts of water and 30 parts of acetone, and vacuum dry at 45°C for 3 hours to obtain dialdehyde corn starch.

[0043] Step 2: By mass, add 1 part of the dialdehyde corn starch obtained in Step 1 to 20 parts of water and 10 parts of 95% ethanol and stir at 25°C. Add 0.03 parts of arginine and continue the reaction for 2 hours. Add 40 ml of ethanol and use a rotary evaporator to evaporate the water at 60°C. Add 100 ml of 95% ethanol to the evaporated liquid until a milky white solid precipitates. Filter to obtain arginine-modified starch.

[0044] Step 3: By mass, 100 parts of ethylene glycol were heated at 150°C for 1 hour, and 1 part of polyvinylpyrrolidone and 0.1 parts of carbon nanotubes were added simultaneously. After stirring rapidly at 160°C for 1 hour, 10 parts of a mixture of 600 mol / L ethylene glycol and 0.1 parts of FeCl3 and 10 parts of a mixed solution of ethylene glycol and 1.2 parts of AgNO3 were added. The reaction was continued at 150°C for 2 hours. After the solution cooled to room temperature, 100 mL of acetone solution was added. After standing for 20 hours, the supernatant was removed, and the solution was washed 4 times by centrifugation with 40 parts of ethanol. The carbon nanotube / silver nanowire composite was obtained by vacuum drying at 60°C.

[0045] Step 4: By mass, add 0.2 parts of the arginine-modified starch obtained in Step 2 to 50 parts of water and stir to dissolve. Add 0.01 parts of N,N-methylenebisacrylamide and 0.02 parts of ammonium persulfate, and then slowly add 2 parts of acrylic acid. 20 minutes after the addition of acrylic acid begins, add 0.004 parts of carbon nanotube / silver nanowire composite. The addition of acrylic acid takes 40 minutes. After all the acrylic acid has been added, continue the reaction for 30 minutes. Treat the above solution with nitrogen for 10 minutes and irradiate it under ultraviolet light for 60 minutes to obtain arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel.

[0046] The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel prepared by the above method exhibits significant application performance and characteristics, particularly its conductive sensing capability. When used in an electrochemical workstation, the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel demonstrated a strain sensitivity (GF) of 2.

[0047] Example 2

[0048] A method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, specifically including the following steps:

[0049] Step 1: Take 7 parts by weight of corn starch with a molecular weight of 180008, add 160 parts of water and stir, then add 2.5 parts of sodium periodate powder, adjust the pH value to 3.5 with 17% hydrochloric acid solution, react at 27°C in the dark for 4.5 hours, wash and filter with 23 parts of water and 32 parts of acetone in sequence, and dry under vacuum at 46°C for 4 hours to obtain dialdehyde corn starch.

[0050] Step 2: By mass, 1.2 parts of the dialdehyde corn starch obtained in Step 1 were added to 22 parts of water and 12 parts of ethanol and stirred at 26°C. 0.06 parts of arginine were added and the reaction continued for 2.5 hours. 45 ml of ethanol was added, and water was evaporated using a rotary evaporator at 62°C. 120 ml of ethanol was added to the evaporated liquid until a milky white solid precipitated. The solid was then filtered to obtain arginine-modified starch.

[0051] Step 3: By mass, 120 parts of ethylene glycol were heated at 155°C for 1.1 hours, and 1.2 parts of polyvinylpyrrolidone and 0.13 parts of carbon nanotubes were added simultaneously. After rapid stirring at 155°C for 1.2 hours, 13 parts of a mixture of 600 mol / L ethylene glycol and 0.13 parts of FeCl3 and 15 parts of a mixed solution of ethylene glycol and 1.5 parts of AgNO3 were added. The reaction was continued at 160°C for 2.1 hours. After the solution cooled to room temperature, 120 mL of acetone solution was added. After standing for 21 hours, the supernatant was removed, and the solution was washed four times by centrifugation with 42 parts of ethanol. The carbon nanotube / silver nanowire composite was obtained by vacuum drying at 65°C.

[0052] Step four: By mass, 0.4 parts of the arginine-modified starch obtained in step two are added to 60 parts of water and stirred to dissolve. Then, 0.02 parts of N,N-methylenebisacrylamide and 0.03 parts of ammonium persulfate are added, followed by the slow dropwise addition of 2.3 parts of acrylic acid. 22 minutes after the addition of acrylic acid begins, 0.005 parts of carbon nanotube / silver nanowire composite are added. The acrylic acid is added over a period of 42 minutes. After all the acrylic acid has been added, the reaction continues for another 32 minutes. The solution is then treated with nitrogen for 12 minutes and irradiated under ultraviolet light for 70 minutes to obtain an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel.

[0053] The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel prepared by the above method exhibits significant application performance and characteristics, particularly its conductive sensing capability. When used in an electrochemical workstation, the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel demonstrated a strain sensitivity (GF) of 3.5.

[0054] Example 3

[0055] A method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, specifically including the following steps:

[0056] Step 1: Take 9 parts by mass of corn starch with a molecular weight of 20,000, add 170 parts of water and stir, then add 3 parts of sodium periodate powder, adjust the pH value to 4 with 18% hydrochloric acid solution, react at 30°C in the dark for 5 hours, wash and filter with 25 parts of water and 35 parts of acetone in sequence, and dry under vacuum at 48°C for 5 hours to obtain dialdehyde corn starch.

[0057] Step 2: By mass, add 1.5 parts of the dialdehyde corn starch obtained in Step 1, 25 parts of water, and 15 parts of ethanol, and stir at 28°C. Add 0.06 parts of arginine and continue the reaction for 3 hours. Add 50 ml of ethanol, and use a rotary evaporator to evaporate the water at 65°C. Add 150 ml of ethanol to the evaporated liquid until a milky white solid precipitates. Filter to obtain arginine-modified starch.

[0058] Step 3: By mass, 140 parts of ethylene glycol were heated at 165°C for 1.3 hours, and 1.6 parts of polyvinylpyrrolidone and 0.16 parts of carbon nanotubes were added simultaneously. After rapid stirring at 160°C for 1.3 hours, 15 parts of a mixture of 600 mol / L ethylene glycol and 0.18 parts of FeCl3 and 20 parts of a mixed solution of ethylene glycol and 1.5 parts of AgNO3 were added. The reaction was continued at 160°C for 2.3 hours. After the solution cooled to room temperature, 130 mL of acetone solution was added. After standing for 23 hours, the supernatant was removed, and the solution was washed four times by centrifugation with 45 parts of ethanol. The carbon nanotube / silver nanowire composite was obtained by vacuum drying at 70°C.

[0059] Step 4: By mass, add 0.5 parts of the arginine-modified starch obtained in Step 2 to 60 parts of water and stir to dissolve. Add 0.03 parts of N,N-methylenebisacrylamide and 0.05 parts of ammonium persulfate, and then slowly add 3 parts of acrylic acid. 25 minutes after the addition of acrylic acid begins, add 0.006 parts of carbon nanotube / silver nanowire composite. The addition of acrylic acid takes 50 minutes. After all the acrylic acid has been added, continue the reaction for 35 minutes. Treat the above solution with nitrogen for 15 minutes and irradiate it under ultraviolet light for 70 minutes to obtain arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel.

[0060] The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel prepared by the above method exhibits significant application performance and characteristics, particularly its conductive sensing capability. When used in an electrochemical workstation, the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel demonstrated a strain sensitivity (GF) of 3.

[0061] Example 4

[0062] A method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, specifically including the following steps:

[0063] Step 1: Take 10 parts by weight of corn starch with a molecular weight of 200,000, add 180 parts of water and stir, then add 3 parts of sodium periodate powder, adjust the pH value to 5 with 20% hydrochloric acid solution, react at 30°C in the dark for 6 hours, wash and filter with 30 parts of water and 40 parts of acetone in sequence, and dry under vacuum at 50°C for 6 hours to obtain dialdehyde corn starch.

[0064] Step 2: By mass, 1.8 parts of the dialdehyde corn starch obtained in Step 1 were added to 28 parts of water and 18 parts of ethanol and stirred at 28°C. 0.15 parts of arginine were added and the reaction continued for 4 hours. 50 ml of ethanol was added, and the water was evaporated using a rotary evaporator at 65°C. 180 ml of ethanol was added to the evaporated liquid until a milky white solid precipitated. The solid was then filtered to obtain arginine-modified starch.

[0065] Step 3: By mass, 180 parts of ethylene glycol were heated at 165°C for 1.3 hours, and 1.6 parts of polyvinylpyrrolidone and 0.15 parts of carbon nanotubes were added simultaneously. After rapid stirring at 160°C for 1.3 hours, 18 parts of a mixture of 600 mol / L ethylene glycol and 0.2 parts of FeCl3 and 20 parts of a mixed solution of ethylene glycol and 1.8 parts of AgNO3 were added. The reaction was continued at 160°C for 2.3 hours. After the solution cooled to room temperature, 130 mL of acetone solution was added. After standing for 22 hours, the supernatant was removed, and the solution was washed four times by centrifugation with 45 parts of ethanol. The carbon nanotube / silver nanowire composite was obtained by vacuum drying at 70°C.

[0066] Step four: By mass, 0.8 parts of the arginine-modified starch obtained in step two are added to 60 parts of water and stirred to dissolve. Then, 0.03 parts of N,N-methylenebisacrylamide and 0.06 parts of ammonium persulfate are added, followed by the slow addition of 4 parts of acrylic acid. 25 minutes after the addition of acrylic acid begins, 0.006 parts of the carbon nanotube / silver nanowire composite are added. The addition of acrylic acid takes 50 minutes. After all the acrylic acid has been added, the reaction continues for 35 minutes. The solution is then treated with nitrogen for 13 minutes and irradiated under ultraviolet light for 80 minutes to obtain an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel.

[0067] An arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel prepared by the above method exhibits significant application performance and characteristics, particularly its conductive sensing capability. When used in an electrochemical workstation, the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel demonstrated a strain sensitivity (GF) of 4.

[0068] Example 5

[0069] A method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, specifically including the following steps:

[0070] Step 1: Take 15 parts by weight of corn starch with a molecular weight of 500,000, add 200 parts of water and stir, then add 4 parts of sodium periodate powder, adjust the pH value to 5 with 20% hydrochloric acid solution, react at 30°C in the dark for 6 hours, wash and filter with 30 parts of water and 40 parts of acetone in sequence, and vacuum dry at 50°C for 8 hours to obtain dialdehyde corn starch.

[0071] Step 2: By mass, add 2 parts of the dialdehyde corn starch obtained in Step 1 to 30 parts of water and 20 parts of ethanol and stir at 30°C. Add 0.2 parts of arginine and continue the reaction for 4 hours. Add 60 ml of ethanol and use a rotary evaporator to evaporate the water at 70°C. Add 200 ml of ethanol to the evaporated liquid until a milky white solid precipitates. Filter to obtain arginine-modified starch.

[0072] Step 3: By mass, 200 parts of ethylene glycol were heated at 170°C for 1.5 hours, and 2 parts of polyvinylpyrrolidone and 0.2 parts of carbon nanotubes were added simultaneously. After rapid stirring at 170°C for 1.5 hours, 20 parts of a mixture of 600 mol / L ethylene glycol and 0.3 parts of FeCl3 and 30 parts of a mixed solution of ethylene glycol and 2 parts of AgNO3 were added. The reaction was continued at 170°C for 2.5 hours. After the solution cooled to room temperature, 150 mL of acetone solution was added. After standing for 24 hours, the supernatant was removed, and the solution was washed 5 times by centrifugation with 50 parts of ethanol. The carbon nanotube / silver nanowire composite was obtained by vacuum drying at 70°C.

[0073] Step 4: By mass, add 1.0 part of the arginine-modified starch obtained in Step 2 to 70 parts of water and stir to dissolve. Add 0.04 parts of N,N-methylenebisacrylamide and 0.08 parts of ammonium persulfate, and then slowly add 5 parts of acrylic acid. 30 minutes after the addition of acrylic acid begins, add 0.008 parts of carbon nanotube / silver nanowire composite. The addition of acrylic acid takes 60 minutes. After all the acrylic acid has been added, continue the reaction for 40 minutes. Treat the above solution with nitrogen for 15 minutes and irradiate it under ultraviolet light for 120 minutes to obtain arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel.

[0074] The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel prepared by the above method exhibits significant application performance and characteristics, particularly its conductive sensing capability. When used in an electrochemical workstation, the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel demonstrated a strain sensitivity (GF) of 4.5.

[0075] See Figure 1 This is a schematic diagram of the reaction of dialdehyde corn starch disclosed in this invention. As can be seen from the diagram, corn starch is converted into dialdehyde corn starch under the oxidation of periodic acid.

[0076] See Figure 2 This is a schematic diagram of the reaction of arginine-modified starch disclosed in this invention; as can be seen from the figure, the aldehyde group in the dialdehyde corn starch undergoes an aldehyde-amine condensation reaction with the amino group in arginine to generate arginine-modified starch.

[0077] See Figure 3 This diagram illustrates the synthesis of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel disclosed in this invention. As can be seen from the diagram, the prepared arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel exhibits a complex structure with multiple interpenetrating and interwoven cross-linked networks formed by covalent cross-linking, ionic cross-linking, hydrogen bond cross-linking, and intermolecular cross-linking. This results in the prepared arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel possessing high strength, good volume stability, and high conductivity and sensing sensitivity.

[0078] See Figure 4 The infrared spectra of the raw materials corn starch, dialdehyde corn starch, and arginine-modified starch disclosed in this invention are shown in the figure. It can be seen from the figure that at 2914 cm⁻¹... -1 The decrease in the absorption peak of the stretching vibration at -CH2 indicates that arginine has been successfully grafted into corn starch; and, at 1640 cm⁻¹ -1 The presence of imine bond absorption indicates that the amide ester has been successfully bonded to the arginine-modified starch; 1604 cm -1 The peak at 1725 cm⁻¹ is a characteristic peak of C=C. -1 These are characteristic peaks of -COH and -C=O; 1027 cm⁻¹ -1 1155cm -1 The characteristic peaks indicate the ratio of the size of the crystalline region to the amorphous region in starch; from the above, we can see that the preparation of arginine-modified starch was successful.

[0079] See Figure 5 The infrared spectra of the corn starch hydrogel, arginine-modified starch hydrogel, and arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel disclosed in this invention are shown in the figures. As can be seen from the figures, 2921 cm⁻¹... -1 The disappearance of the stretching vibration absorption peak at -CH2 indicates that arginine was successfully grafted into corn starch. A comparison of the infrared spectra of pure corn starch membranes revealed that the arginine-modified starch hydrogel membrane had a peak density of 1708 cm⁻¹. -1 A new absorption peak was observed at 3375 cm⁻¹, which was attributed to the characteristic peak of the C=O stretching vibration, indicating the successful introduction of the carbonyl group from L-arginine onto the starch. The decrease in the size of this peak after the introduction of the carbon nanotube / silver nanowire composite further confirms the successful incorporation of the composite. Furthermore, the infrared spectra of arginine-modified starch and arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel films showed a peak at 3375 cm⁻¹. -1 It also showed characteristic peaks different from those of simple starch absorption peaks, mainly due to the formation of amide esters after L-arginine cross-links with corn starch, which belong to the -NH2 absorption peak here. Furthermore, at 1640 cm⁻¹... -1 The presence of imine bond absorption indicates that the amide ester has been successfully attached to the arginine-modified starch hydrogel membrane. (1007 cm⁻¹) -1 1155cm -1 1440cm -1 The decrease in the characteristic peak indicates enhanced molecular interactions between polymers. From the above, we can see that the preparation of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel film was successful.

[0080] Comparison Example

[0081] By mass, 0.2 parts of starch were added to 10 parts of distilled water, stirred and clarified, and then 0.04 parts of N,N-methylenebisacrylamide and 0.08 parts of ammonium persulfate were added to continue the reaction. Then, 3 parts of acrylic acid were slowly added and stirred for 30 minutes. Finally, the mixture was irradiated under ultraviolet light for 15 minutes to obtain starch hydrogel.

[0082] An arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel prepared according to the above method exhibits significant application performance and characteristics, particularly its conductive sensing capability. When the starch hydrogel was used to test an electrochemical workstation, its strain sensitivity (GF) was 0.5. The comparison of hydrogel strain sensitivity (GF) results is shown in Table 1.

[0083] Table 1. Comparison of strain sensitivity (GF) results of arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogels prepared in Examples 1-5

[0084] Example 1 2 Example 2 3.5 Example 3 3 Example 4 4 Example 5 4.5 Comparison Example 0.5

[0085] Polymer-based hydrogels, prepared by mixing synthetic polymers or inorganic components with natural polymers, can achieve tunable mechanical properties and offer numerous advantages in conductive applications. This invention discloses a method for preparing arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogels and their applications. This method uses arginine-modified corn starch as raw material, based on the principle of free radical polymerization, with acrylic acid and N,N-methylenebisacrylamide as crosslinking agents, and ammonium persulfate as an initiator. Finally, a carbon nanotube / silver nanowire composite is introduced to significantly improve the hydrogel's conductivity. Arginine-modified starch / polyacrylic acid carbon nanotube / silver nanowire hydrogels are prepared using both physical and chemical crosslinking. The prepared hydrogel exhibits significantly improved mechanical strength and sensing performance, effectively overcoming the shortcomings of existing starch-based hydrogels, such as poor mechanical strength, weak molecular chain interactions in the gel network, and poor sensing performance. The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel prepared by this invention possesses good conductive and sensing properties.

[0086] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, characterized in that, Includes the following steps: 1) Dissolve corn starch in water, add sodium periodate, adjust the pH to 3-5, react in the dark, filter, wash and dry to obtain dialdehyde corn starch. 2) Add the dialdehyde corn starch obtained in step 1) to a mixture of ethanol and water, then add arginine, stir and react, add ethanol, and then evaporate by rotary evaporation to obtain arginine-modified starch. 3) Add polyvinylpyrrolidone and carbon nanotubes to heated ethylene glycol, stir evenly, add a mixed solution of ethylene glycol and FeCl3 and a mixed solution of ethylene glycol and AgNO3, keep the reaction at the temperature, add acetone solution, let stand to remove the supernatant, wash by centrifugation, and dry under vacuum to obtain carbon nanotube / silver nanowire composite. 4) Dissolve the arginine-modified starch obtained in step 2) in water by stirring, add N,N-methylenebisacrylamide and ammonium persulfate, stir evenly, start adding acrylic acid dropwise, then add the carbon nanotube / silver nanowire composite obtained in step 3), stir and react, purge under nitrogen, and after ultraviolet irradiation, obtain arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel. In step 4), the mass ratio of arginine-modified starch: N,N-methylenebisacrylamide: ammonium persulfate: acrylic acid: carbon nanotube / silver nanowire composite is (0.2~1.0): (0.01~0.04): (0.02~0.08): (2~5): (0.004~0.008).

2. The preparation method of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 1, characterized in that, In step 1), the mass ratio of corn starch:water:sodium periodate is (5~15):(150~200):(2~4); the temperature of the light-protected reaction is 25~30℃, and the reaction time is 4~6 hours; the drying conditions are vacuum drying at 45~50℃ for 3~8 hours; the molecular weight of the corn starch is 16000~500000.

3. The preparation method of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 1, characterized in that, In step 1), the pH value is adjusted using a dilute hydrochloric acid solution with a mass fraction of 16%~20%; the washing conditions are: washing three times with water and acetone in sequence, with a mass ratio of water to acetone of (20~30):(30~40).

4. The preparation method of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 1, characterized in that, In step 2), the mass ratio of the dialdehyde corn starch to arginine is (1~2):(0.03~0.2); in the mixture of ethanol and water, the mass ratio of ethanol to water is (10~20):(20~30), and the purity of ethanol is 95%; the temperature of the stirring reaction is 25~30℃, and the stirring reaction time is 2~4 hours; the temperature of rotary evaporation is 60~70℃.

5. The preparation method of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 1, characterized in that, In step 3), the mass ratio of polyvinylpyrrolidone: carbon nanotubes: FeCl3: AgNO3 is (1~2):(0.1~0.2):(0.1~0.3):(0.3~0.5); 100~200 parts by mass of ethylene glycol and 100~150 ml of acetone are added to every 0.1~0.2 parts by mass of carbon nanotubes; every 0.1~0.3 parts by mass of FeCl3 is mixed with 10~20 parts by mass of ethylene glycol; every 1.2~2 parts by mass of AgNO3 is mixed with 10~30 parts by mass of ethylene glycol. After standing for 20-24 hours to remove the supernatant, the precipitate is washed by centrifugation, then washed with anhydrous ethanol. After washing three times, it is dried under vacuum at 60-70℃.

6. The method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 1, characterized in that, In step 3), the carbon nanotubes comprise 95% by mass, are single-arm carbon nanotubes, have a conductivity greater than 2000 S / cm, and a specific surface area greater than 980 m². 2 / g; the mass percentage of silver nanowires is 95%, the diameter of the silver nanowires is 90nm, and the length of the silver nanowires is 50um; the heating temperature is 150~170℃; the stirring conditions are stirring at 150~170℃ for 1~1.5 hours; the heat preservation reaction conditions are reacting at 150~170℃ for 2~2.5 hours; the standing time is 20~24 hours; the number of washing times is 3~5 times.

7. The preparation method of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 1, characterized in that, In step 4), during preparation, 0.2 to 1.0 parts by weight of arginine-modified starch are first dissolved in 50 to 70 parts by weight of water.

8. The method for preparing an arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 1, characterized in that, In step 4), the stirring reaction time is 30-40 minutes; the nitrogen purging time is 10-15 minutes; and the ultraviolet irradiation time is 60-120 minutes.

9. An arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel, characterized in that, The arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel was prepared using any one of claims 1-8.

10. The application of the arginine-modified starch / polyacrylic acid / carbon nanotube / silver nanowire hydrogel according to claim 9 in conductive sensing.